HUBUNGAN ANTARA STRES KERJA DENGAN KELELAHAN KERJA YANG DIKENDALIKAN UMUR DAN MASA KERJA PADA PERAWAT RUMAH SAKIT SWASTA X DI KOTA YOGYAKARTA Tinjauan Aspek Keselamatan Dan Kesehatan Kerja (K3) - , ROCHFIKA SULEIMAN; , Prof. Dr. dr. Adi Heru Sutomo, M.Sc., D. Comm.Nutr., DLSHTM., ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nurse is a profession who has high level of stress and work fatigue. Many numbers of monotonic tasks become a stressor for the nurse. Sometimes the nurse face emotional patient. There are some physical symptoms suffered by the nurses at the X Private Hospital in Yogyakarta, such as stomachache, headache, and hypertension, and the psychological symptoms such as cannot concentrating on their work, feeling tired, and bad tempered. To analyze work stress and work fatigue which are associated by age and working period on the nurses at X Private Hospital in Yogyakarta city. This research is a quantitative research with cross sectional research design. The samples are taken using proportional stratified random sampling method. The data which being obtained are processed using Partial correlation test. There is a correlation between work stress and work fatigue which controlled by the age and working period (r : 0.634) and (p : 0,000), There is a correlation between work stress and work fatigue which controlled by the age (r : 0.629) and (p : 0,000), There is a correlation between work stress and work fatigue which controlled by the working period (r :0,633) and ( p : 0,00). There is a correlation between work stress and work fatigue which are associated by the age and working period, There is a correlation between work stress and work fatigue which are associated by the age, There is a correlation between work stress and work fatigue which are associated by the working period.